INTERACTIVE TEACHING METHODS IN ENGLISH LANGUAGE LESSONS - Mahkamova Makhmuda (Journals Park Publishing, 2022)
The article deals with one of the ways to modernize education on a competence - based basis, namely, through the use of interactive forms of education in teaching. Interactive teaching methods provide solutions to educational problems in various aspects. Possession of interactive learning technology contributes to the development of students' qualities that meet the requirements prescribed in the state standards of the new generation.
Keywords: interactive teaching methods, dialog communication, teaching methods, innovative forms of learning.